Liposome Photosensitizer with Enzyme from Black Soybean Tempeh: Formula Optimization and In Vitro Thrombolytic Activity Evaluation - Azzahra, Farah Daffa; Mulyani, Laida Neti; Sabrina, Tia; Fithri, Najma Annuria (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Stroke and myocardial infarction contributed significantly as the leading causes of global mortality rate, both commonly caused by thrombosis. Black soybean tempeh (BSBT), a traditional Indonesian food fermented with Rhizopus oligosporus fungus is rich in proteolytic enzymes, with potential to be utilized for thrombosis related ailments. Herein, we report the first findings of BSBT enzymatic activity and its subsequent formulation into liposomal system as a thrombolytic. Additionally, we incorporated photosensitizer dyes into the liposomes, phycocyanin and fluoresecein, creating a photothermally active therapeutic delivery system. Liposomes containing BSBTwere formulated using soy lecithin and tween 80, whichwere then subjected to evaluations including size, PDI, zeta potential, morphological, and stability studies. Furthermore, we observed their photothermal efficiency and thrombolytic activity using whole blood clot in vitro model. BSBT crude and purified extract produced satisfactory enzymatic activity, stable at neutral pH (∼7) and maintained stable activity at temperatures of ∼60◦C. Liposome formulation was spherical with a particle size of 607.8 nm; PDI of 0.339; and zeta potential of -24.2 mV. BSBT crude extract and purified enzyme at a concentration of 100% gave 51.28 and 56.05% thrombolytic activity. Based on the test results obtained, the optimum formula of photosensitizer liposomes produced had high encapsulation efficiency, with photothermal efficiency of 57.66 and 44.23% for Lip-Flu and Lip-Phy respectively. The formulations with laser exposure generated good thrombolytic activity (∼55-56%) comparable with nattokinase. Based on these findings, liposomal delivery of BSBT enzymes can maintain proteolytic activity, providing the first insights for thrombolytic purposes of BSBT enzymes.